Inhibition of ASCT2 induces hepatic stellate cell senescence with modified proinflammatory secretome through an IL-1α/NF-κB feedback pathway to inhibit liver fibrosis - Feixia Wang; Zhanghao Li; Li Chen; Ting Yang; Baoyu Liang; Zili Zhang; Jiangjuan Shao; Xuefen Xu; Guoping Yin; Shijun Wang; Hai Ding; Feng Zhang; et al. (Elsevier, 2022)
Senescence of activated hepatic stellate cells (aHSCs) is a stable growth arrest that is implicated in liver fibrosis regression. Senescent cells often accompanied by a multi-faceted senescence-associated secretory phenotype (SASP). But little is known about how alanine-serine-cysteine transporter type-2 (ASCT2), a high affinity glutamine transporter, affects HSC senescence and SASP during liver fibrosis. Here, we identified ASCT2 is mainly elevated in aHSCs and positively correlated with liver fibrosis in human and mouse fibrotic livers. We first discovered ASCT2 inhibition induced HSCs to senescence in vitro and in vivo. The proinflammatory SASP were restricted by ASCT2 inhibition at senescence initiation to prevent paracrine migration. Mechanically, ASCT2 was a direct target of glutaminolysis-dependent proinflammatory SASP, interfering IL-1α/NF-κB feedback loop via interacting with precursor IL-1α at Lys82. From a translational perspective, atractylenolide III is identified as ASCT2 inhibitor through directly bound to Asn230 of ASCT2. The presence of -OH group in atractylenolide III is suggested to be favorable for the inhibition of ASCT2. Importantly, atractylenolide III could be utilized to treat liver fibrosis mice. Taken together, ASCT2 controlled HSC senescence while modifying the proinflammatory SASP. Targeting ASCT2 by atractylenolide III could be a therapeutic candidate for liver fibrosis.